Medial Pelvic Migration of the Lag Screw after Intramedullary Nailing for Trochanteric Femoral Fracture - Kohei Kuroshima; Koichi Kasahara; Shinsuke Kihara; Yoshifumi Harada; Masatoshi Sumi (Case Reports in Orthopedics)
Internal fixation with intramedullary nails has gained popularity for the treatment of trochanteric femoral fractures, which are common injuries in older individuals. The most common complications are lag screws cut-out from the femoral head and femoral fracture at the distal tip of the nail. Herein, we report a rare complication of postoperative medial pelvic migration of the lag screw with no trauma. The patient was subsequently treated by lag screw removal via laparoscopy. This case suggests that optimal fracture reduction, adequate position of the lag screw, and careful attention to set screw insertion are important to prevent complications. Additionally, laparoscopic surgery might be able to remove the lag screw more safely than removal from the femoral side.